An Elegy to Cities’ Reciter of Elegies (A Critique on the Book Cities’ Reciter of Elegies) - Arash Amraei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The complete poetical work of Khaghani (Khaghani’s Divan) is one of the worthy works of Persian literature that is famous for being difficult to obtain and understand. Thus, Khaghani's Divan has been less favored by commentators than other Divans of Persian poetry. In the meantime, the felicity and excerpts have impeded Khaghani's Divan as well, and several excerpts from Khaghani's odes (qasidas) have been described and published. One of these works is a book entitled " Cities' Reciter of Elegies ", written by Mohammad Reza Barzegar Khaleghi and Mohammad Hussein Mohammadi and published by Zovvar Publications in 224 pages. The present paper reviews this work and also points to some of the falsehoods and inaccuracies that have been attributed to it. Problems that will be discussed in detail include using the works of others without citing them, silence against difficult and problematic Khaghani’s verses, misinterpretations of certain verses, confusing sources, many typographical errors, and omitting some aspects of Khaghani’s poetry.